Grothendieck-Serre correspondence - Grothendieck, A.; Colmez, Pierre; Serre, Jean-Pierre; Maclean, Catriona (Providence : American Mathematical Society, 2004)
This book presents an introduction to the development of algebraic geometry during the years 1955-1965. It is suitable for specialists in algebraic geometry, and mathematical historians.
Opposite pages bear duplicate numbering.
Includes bibliographical references and index.
Parallel French and English text.
Keywords: Grothendieck, A. -- Correspondence; Mathematicians -- France -- Correspondence; Algebraic Geometry